2008
DOI: 10.1016/j.pain.2007.04.029
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral activation during motor imagery in complex regional pain syndrome type 1 with dystonia

Abstract: The pathogenesis of dystonia in Complex Regional Pain Syndrome type 1 (CRPS-1) is unclear. In primary dystonia, functional magnetic resonance imaging (fMRI) has revealed changes in cerebral networks during execution of movement. The aim of this study was to determine cerebral network function in CRPS-1 patients with dystonic postures. Cerebral processing related to both execution and imagining of hand movements in patients and controls was assessed with fMRI. Eight CRPS-1 patients with dystonic postures of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 36 publications
4
50
0
2
Order By: Relevance
“…In a number of studies, typical clinical CRPS symptoms could be directly linked to this CNS reorganization, such as impaired tactile perception (hypoesthesia) in the absence of peripheral nerve lesions, dystonia, or reduced finger-tapping frequency as a marker of motor impairment. 32,48,51 Many studies provided evidence for a close relationship between chronic pain and CNS reorganization in somatosensory and Changes in S1 representation, pain intensity, and discrimination ability during the course of therapy in a single patient. BOLD contrast received from cortical maps on S1 contralateral to the healthy (left image) and to the CRPS-affected side (right, images of 3 consecutive measurements).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a number of studies, typical clinical CRPS symptoms could be directly linked to this CNS reorganization, such as impaired tactile perception (hypoesthesia) in the absence of peripheral nerve lesions, dystonia, or reduced finger-tapping frequency as a marker of motor impairment. 32,48,51 Many studies provided evidence for a close relationship between chronic pain and CNS reorganization in somatosensory and Changes in S1 representation, pain intensity, and discrimination ability during the course of therapy in a single patient. BOLD contrast received from cortical maps on S1 contralateral to the healthy (left image) and to the CRPS-affected side (right, images of 3 consecutive measurements).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas patients with CRPS with dystonia were excluded in the study by Maihöfner et al 48 to achieve a homogeneous patient group, patients with CRPS I with dystonia were explicitly examined by fMRI in a recent study by Gieteling et al 51 The distribution of cerebral activations was assessed during both motor execution and imaging of movement of affected as well as unaffected limbs and compared with the activation pattern in healthy controls. There were no differences between patients and controls when they executed movements or when they imagined moving their unaffected hand.…”
Section: Motor Systemmentioning
confidence: 99%
“…The hand laterality task is considered to provide a measure of the integration between information processing, working body schema, and premotor processes activating a restricted parietofrontal network (9). In a particular subset of CRPS patients, Gieteling et al (10) showed significantly reduced cortical activation in areas spanning motor planning, sensory integration, autonomic function, and pain during conscious imagined movement (compared with healthy controls and compared with unaffected hand). Gustin et al (3) suggest that the pain arising from motor imagery is linked to the strength of motor cortex stimulation, on the basis that the analgesia from intense electrical stimulation of the primary motor cortex inhibits neuronal activity in the thalamus.…”
Section: To the Editorsmentioning
confidence: 99%
“…We have also seen patients who get worse with implicit motor imagery; although in our experience, they are rare. Our treatment approach to these patients has been to make an even more conservative exposure to movement by preceding graded motor imagery (itself a more conservative version of mirror therapy [9,10]) with the observation of movement in others. We adopted this approach on the basis of extensive work that demonstrates that motor processes can be activated by watching others do functionally-relevant movements (the so-called mirror neuron system [for review, see ref.…”
Section: To the Editorsmentioning
confidence: 99%
“…In einer weiteren Studie bei CRPS wurden verringerte Schmerzeinschätzungen während und nach einem Spiegeltraining der nicht beeinträchtigten Hand gefunden [McCabe et al, 2003]. Während einer fMRI-Messung sollten CRPS-Patienten mit dystonischen Handpositionen echte und vorgestellte Handbewegungen ausführen [Gieteling et al, 2008]. Im Vergleich zu gesunden Probanden zeigte sich bei den Patienten bei vorgestellten Bewegungen der beeinträchtigten Hand eine verringerte Aktivierung des ipsilateralen prämotorischen Kortex und des angrenzenden präfrontalen Kortex.…”
Section: Muskelschmerzunclassified